Exploring role of probiotics and Ganoderma lucidum extract powder as solid carriers to solidify liquid self-nanoemulsifying delivery systems loaded with curcumin. (15th December 2020) - Khursheed, Rubiya; Singh, Sachin Kumar; Wadhwa, Sheetu; Gulati, Monica; Awasthi, Ankit; Kumar, Rajan; Ramanunny, Arya Kadukkattil; Kapoor, Bhupinder; Kumar, Pushpendra; Corrie, Leander
Highlights: Curcumin loaded liquid SNEDDS were prepared Liquid SNEDDS we reconverted to free-flowing powder form (Solid SNEDDS) using Ganoderma lucidium extract powder (GLEP) and probiotics (PB) Prepared solid SNEDDS exhibited excellent micromeritic properties Solid SNEDDS were converted into spheroids Dissolution rate and permeability of curcumin in the final spheroid formulation were substantially improved than those for the pure drug Abstract: Solid self-nanoemulsifying drug delivery system (S-SENDDS) containing Curcumin (CRM) were prepared using combination of Ganoderma lucidum extract powder (GLEP) and probiotics (PB) as carriers. Liquid SNEDDS containing CRM were prepared by mixing Capmul MCM, Labrafil M1944CS, Tween 80 and Transcutol P. These were further spray dried and finally converted into spheroids. The droplet size of reconstituted S-SNEDDS powder and spheroids was found in the range of 35 to 37 nm, zeta potential in the range of - 21.48 to -23.22 mV and drug loading in the range of 95-96%. The release of drug from formulations was found to be more than 90%. Similarly, significant improvement (p < 0.05) in permeability of CRM was observed through SNEDDS using Caco2 cell lines. The non-significant difference (p> 0.05) in drug loading, droplet size, dissolution rate and angle of repose between L-SNEDDS and S-SNEDDS indicated the potential of GLEP-PB to produce stable SNEDDS.